Blossoming Success: A SWOT-Infused Strategy for Flower Shop - Jana Sandra; Sigit Saptono; Rahmani Fitra (Escalate : Economics and Business Journal, 2023)
This study aims to assess the strategic landscape of XYZ Flower Shop by conducting a comprehensive SWOT analysis, with a focus on its internal strengths and weaknesses, as well as external opportunities and threats. The research involved gathering data through questionnaires distributed to the shop's owners and employees. The SWOT analysis was carried out by identifying strengths such as quality and diverse products, affordable pricing, strategic location, delivery services, and a comfortable store concept. Weaknesses encompassed perishable and non-durable raw materials, suboptimal promotion, and a lack of specialized marketing personnel. External factors revealed opportunities such as a loyal customer base, evolving societal lifestyles, technological advancements, and a lack of product substitutes, along with threats like high competition in West Jakarta and strong buyer bargaining power. The SWOT analysis generated several strategic alternatives, including strategies to leverage strengths to capitalize on opportunities (S-O), mitigate weaknesses through opportunities (W-O), employ strengths to combat threats (S-T), and address weaknesses to defend against threats (W-T). the priority strategy for XYZ Flower Shop involves harnessing its quality and diverse products to foster growth.